Adverse reactions after Covid-19 vaccination in persons affected by leprosy: A scoping review - Senthilkumar Ramasamy; Abhiruchi Galhotra; Sanjana Agrawal (Journal of Family Medicine and Primary Care)
Background: Leprosy reactions are the main pathway leading to severe nerve damage and disability. These reactions can occur at any time. The coronavirus disease 2019 (Covid-19) pandemic led to a catastrophic loss of human life and has had a devastating impact on persons affected by leprosy. Objective: To achieve deep insight into the subject of adverse reactions acquired after Covid vaccinations in persons affected by leprosy through a literature review. Materials and Methods: A scoping review was conducted in the studies published between July 2021 and June 2022 using the Preferred Reporting Items for Systematic Review and Meta-Analysis Extension for Scoping Reviews (PRISMA-ScR) checklist. Results: Using the search strategy, a total of 130 articles were found, of which five were relevant to the study. The adverse reactions were acquired mostly in males [9 (81.8%)]; the majority of them belong to borderline tuberculoid [4 (36.4%)], and most of them were released from treatment (multi-drug therapy) [7 (63.6%)]. Conclusion: Surveillance and management of adverse events following immunization (AEFI) are essential; even minor AEFI should be reported and documented in a line list.